Antimicrobial Photodynamic Therapy Involving a Novel Photosensitizer Combined With an Antibiotic in the Treatment of Rabbit Tibial Osteomyelitis Caused by Drug-Resistant Bacteria - Yin, Xiujuan; Fang, Ziyuan; Fang, Yan; Zhu, Lin; Pang, Jinwen; Liu, Tianjun; Zhao, Zhanjuan; Zhao, Jianxi (Frontiers in Microbiology, 2022)
Osteomyelitis is a deep tissue inflammation caused by bacterial infection. The persistent infection will lead to dissolution and necrosis of bone tissue. Because of the extensive use of antibiotics, osteomyelitis caused by drug-resistant bacteria is one of the urgent problems to be solved by orthopedic surgeons. Photodynamic antibacterial biotherapy has gradually attracted people's attention. Its advantages are a broad antibacterial spectrum, drug unresistance and no toxic side effects. This experiment explored the impact of new photosensitizers LD4-PACT and LD4-PACT combined with antibiotics on osteomyelitis. The experimenters selected 24 New Zealand white rabbits and randomly divided them into control group, antibiotic group, PACT group and PACT+ antibiotic group for treatment. To evaluate the effect of LD4-PACT and LD4-PACT combined with antibiotics on rabbit tibial osteomyelitis through microbiology, histology and radiology. In the microbiological study, the bacterial reduction rate of the PACT group and PACT+ antibiotic group reached more than 99.9% four weeks after treatment (P < 0.001). In the histological study, the repair of damaged bone tissue can be seen in the PACT group. In contrast, bone repair in the PACT+ antibiotic group is significantly greater than that in the PACT group. X-ray Norden score showed that the severity of bone tissue destruction or defect was PACT+ antibiotic group < PACT group < antibiotic group < control group.